Mindfulness diverse perspectives on its meaning, origins and applications - Williams, J. Mark G.; Kabat-Zinn, Jon (Routledge, 2013)
This book presents the work of internationally renowned experts in the fields of Buddhist scholarship and scientific research, as well as looking at the implementations of mindfulness in healthcare and education settings. Contributors consider the use of mindfulness throughout history and look at the actual meaning of mindfulness whilst identifying the most salient areas for potential synergy and for potential disjunction.